A New Educational Model for Criminality Prevention - Emilian M. DOBRESCU
Solon said that, in order to be free, a citizen had to study; education was the ground of democracy and in Athens there was no illiterate citizen. The education was both of the body as well as of the soul in a natural continuity... Plato was even aware that in all that there was, there was a core of “dissension” (entropie) that sooner or later led to the fall. He tried to set a fortress model that would minimize the effects of this core of destruction. In the dialogue entitled „Republica”, he pointed out that it was in the power of man to minimize the evil and to build a harmonious fortress that would prevent the destruction. The idea of harmony, which is to be found also in music and mathematics, is extended also to the relations between people.